Analisis Pengendalian Kualitas Mengidentifikasi Kecacatan Produk X Dengan Metode Statistical Proses Control di PT. XY - Swendi, Vincentius Rico; Efelina, Vita (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
PT.XY is a manufacturing company engaged in Paper Products in Indonesia. Product X is one of the products that is produced and is widely used for activities because it is safe and comfortable to use. The number of defects in product X is more than other types of products. Based on data from the quality control department of PT. XY shows that product X gets results that are not in accordance with predetermined standards and quality. The purpose of this study is to identify the types of defects and determine the factors that often occur from the main causes of defects that occur in product X from the Rewinding process using the Statistical Process Control method. There are several tools that are used to identify the main causes of defects in the production process of product X. Among these tools consist of several, namely, check sheets, Pareto diagrams, cause and effect diagrams, histograms, and control charts. The results showed that the most common defect in product X was Uneven Cut. Therefore, there are several factors that cause defects in product X due to method factors, machine factors, environmental factors, and human factors which greatly influence production.